IMPROVING STUDENTS’ READING COMPREHENSION THROUGH GRAMMAR -TRANSLATION METHOD - Abrueva , Malika Zafarovna (Educational Research in Universal Sciences, 2023)
Reading is considered as an important part of language skill. It became vital in the process of learning a language. However, many researches showed that many learners have difficulties with this skill. This article is mainly aimed to identify the effect of reading comprehension improved through grammar translation method. A number of researches showed that there was significant improvement of the students’ skill in reading comprehension through learning it with the help of grammar-translation method in which it was found out that the level improved from insufficient to good. This article shows how the usage of grammar-translation method can help to improve students’ reading skill through some researches that were done in this field.